3D-printed poly(Ɛ-caprolactone) scaffold with gradient mechanical properties according to force distribution in the mandible for mandibular bone tissue engineering. (April 2020) - Zamani, Yasaman; Amoabediny, Ghassem; Mohammadi, Javad; Seddiqi, Hadi; Helder, Marco N.; Zandieh-Doulabi, Behrouz; Klein-Nulend, Jenneke; Koolstra, Jan Harm
Abstract: In bone tissue engineering, prediction of forces induced to the native bone during normal functioning is important in the design, fabrication, and integration of a scaffold with the host. The aim of this study was to customize the mechanical properties of a layer-by-layer 3D-printed poly(ϵ-caprolactone) (PCL) scaffold estimated by finite element (FE) modeling in order to match the requirements of the defect, to prevent mechanical failure, and ensure optimal integration with the surrounding tissue. Forces and torques induced on the mandibular symphysis during jaw opening and closing were predicted by FE modeling. Based on the predicted forces, homogeneous-structured PCL scaffolds with 3 different void sizes (0.3, 0.6, and 0.9 mm) were designed and 3D-printed using an extrusion based 3D-bioprinter. In addition, 2 gradient-structured scaffolds were designed and 3D-printed. The first gradient scaffold contained 2 regions (0.3 mm and 0.6 mm void size in the upper and lower half, respectively), whereas the second gradient scaffold contained 3 regions (void sizes of 0.3, 0.6, and 0.9 mm in the upper, middle and lower third, respectively). Scaffolds were tested for their compressive and tensile strength in the upper and lower halves. The actual void size of the homogeneous scaffolds with designed void size of 0.3, 0.6, and 0.9 mm was 0.20, 0.59, and 0.95 mm, respectively. FE modeling showed that during opening and closing of the jaw, the highest force induced on the symphysis was a compressive force in the transverse direction. The compressive force was induced throughout the symphyseal line and reduced from top (362.5 N, compressive force) to bottom (107.5 N, tensile force) of the symphysis. Compressive and tensile strength of homogeneous scaffolds decreased by 1.4-fold to 3-fold with increasing scaffold void size. Both gradient scaffolds had higher compressive strength in the upper half (2 region-gradient scaffold: 4.9 MPa; 3 region-gradient scaffold: 4.1 MPa) compared with the lower half (2 region-gradient scaffold: 2.5 MPa; 3 region-gradient scaffold: 2.7 MPa) of the scaffold. 3D-printed PCL scaffolds had higher compressive strength in the scaffold layer-by-layer building direction compared with the side direction, and a very low tensile strength in the scaffold layer-by-layer building direction. Fluid shear stress and fluid pressure distribution in the gradient scaffolds were more homogeneous than in the 0.3 mm void size scaffold and similar to the 0.6 mm and 0.9 mm void size scaffolds. In conclusion, these data show that the mechanical properties of 3D-printed PCL scaffolds can be tailored based on the predicted forces on the mandibular symphysis. These 3D-printed PCL scaffolds had different mechanical properties in scaffold building direction compared with the side direction, which should be taken into account when placing the scaffold in the defect site. Our findings might have implications for improved performance and integration of scaffolds with native tissue. Graphical abstract: Image 1 Highlights: Jaw opening induced higher compression to upper versus lower parts of the symphysis. All scaffolds had higher compressive strength in building versus side direction. Gradient scaffolds had higher compressive strength in upper versus lower half. Gradient scaffolds fit the force distribution in the symphysis during jaw opening. Fluid shear stress and pressure were rather homogeneous in the gradient scaffolds.